Kaempferol attenuated diabetic nephropathy by reducing apoptosis and promoting autophagy through AMPK/mTOR pathways - Sheng, Hongqin; Zhang, Duo; Zhang, Jiaqi; Zhang, Yanmei; Lu, Zhaoyu; Mao, Wei; Liu, Xusheng; Zhang, Lei (Frontiers in Medicine, 2022)
Diabetic nephropathy (DN) has become the major cause of end-stage renal disease worldwide, which is intimately correlated with autophagy flux inhibition and podocyte dysfunction. Kaempferol (KPF) belongs to the family of natural flavonols. It has the promotion of autophagy and inhibition of apoptosis properties in the development of miscellaneous diseases, but these functions in DN have not yet been elucidated. Herein, we used db/db mice to evaluate the protective role of KPF on podocytes via autophagy in the development of DN. We demonstrated that KPF treatment significantly attenuated diabetes-induced albuminuria and glycolipid metabolism dysfunction. In addition, KPF alleviated mesangial matrix expansion, glomerular basement membrane thickening, and loss or fusion of podocytes. Mechanistically, KPF treatment regulated the expression of autophagic proteins (upregulated LC3II, Beclin-1, Atg7, and Atg 5, and downregulated p62/SQSTM1), accompanied by inhibited renal apoptosis (downregulated Caspase 3 and Bax, and upregulated Bcl-2). KPF could significantly regulate the AMPK/mTOR signaling pathways by increasing p-AMPK and decreasing p-mTOR expressions. In conclusion, KPF might have a protective effect on DN through reduced apoptosis and enhanced podocyte autophagy, which were correlated with regulating AMPK/mTOR pathways.